Salmonella enterica serovar Typhimurium exploits inflammation to modify swine intestinal microbiota. - Rosanna eDrumo; Rosanna eDrumo; Michele ePesciaroli; Michele ePesciaroli; Jessica eRuggeri; Michela eTarantino; Barbara eChirullo; Claudia ePistoia; Paola ePetrucci; Nicola eMartinelli; Livia eMoscati; Elisabetta eManuali; et al. (Frontiers in Cellular and Infection Microbiology, 2016)
Salmonella enterica serovar Typhimurium is an important zoonotic gastrointestinal pathogen responsible for foodborne disease worldwide. It is a successful enteric pathogen because it has developed virulence strategies allowing it to survive in a highly inflamed intestinal environment exploiting inflammation to overcome colonization resistance provided by intestinal microbiota. In this study, we used piglets featuring an intact microbiota, which naturally develop gastroenteritis, as model for salmonellosis. We compared the effects on the intestinal microbiota induced by a wild type and an attenuated S. Typhimurium in order to evaluate whether the modifications are correlated with the virulence of the strain. This study showed that Salmonella alters microbiota in a virulence-dependent manner. We found that the wild type S. Typhimurium induced inflammation and a reduction of specific protecting microbiota species (SCFA-producing bacteria) normally involved in providing a barrier against pathogens. Both these effects could contribute to impair colonization resistance, increasing the host susceptibility to wild type S. Typhimurium colonization. In contrast, the attenuated S. Typhimurium, which is characterized by a reduced ability to colonize the intestine, and by a very mild inflammatory response, was unable to successfully sustain competition with the microbiota.